2010
DOI: 10.1186/1471-2229-10-268
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic characterization of iron deficiency responses in Cucumis sativusL. roots

Abstract: BackgroundIron deficiency induces in Strategy I plants physiological, biochemical and molecular modifications capable to increase iron uptake from the rhizosphere. This effort needs a reorganization of metabolic pathways to efficiently sustain activities linked to the acquisition of iron; in fact, carbohydrates and the energetic metabolism has been shown to be involved in these responses. The aim of this work was to find both a confirmation of the already expected change in the enzyme concentrations induced in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
74
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 57 publications
13
74
2
Order By: Relevance
“…Down regulated detoxifying proteins in Fe-deprived conditions, viz. CAT2 (CATALASE 2; AT4G35090) proteins and PA2 (PEROXIDASE 2; AT5G06720) proteins, were reported in some plants (Donnini et al, 2010;Rodríguez-Celma et al, 2011). These are enzymes that help in the conversion of H 2 O 2 (hydrogen peroxide) to H 2 O (water) and oxygen.…”
Section: Rapeseed (Brassica Napus)mentioning
confidence: 99%
“…Down regulated detoxifying proteins in Fe-deprived conditions, viz. CAT2 (CATALASE 2; AT4G35090) proteins and PA2 (PEROXIDASE 2; AT5G06720) proteins, were reported in some plants (Donnini et al, 2010;Rodríguez-Celma et al, 2011). These are enzymes that help in the conversion of H 2 O 2 (hydrogen peroxide) to H 2 O (water) and oxygen.…”
Section: Rapeseed (Brassica Napus)mentioning
confidence: 99%
“…One or more of the iron deficiency-inducible subgroup Ib bHLH proteins (Heim et al, 2003), bHLH038, bHLH039, bHLH100, and bHLH101, needs to be present and probably forms dimers with FIT for the induction to take place (Wang et al, 2007(Wang et al, , 2013Yuan et al, 2008). This was found to be only a small part of the extensive posttranscriptional regulation of the iron uptake system (Brumbarova and Bauer, 2005;Brumbarova et al, 2008;Donnini et al, 2010;Rellán-Alvarez et al, 2010;Lan et al, 2011). AHA1 and AHA2 activity is regulated by phosphorylation of a single amino acid (Fuglsang et al, 2007;Haruta et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The primary iron uptake response genes for ferric reductase FRO1, iron transporter IRT1 (Waters et al 2007), and H + -ATPase HA1 (Santi et al 2005) have been identified from cucumber. More recently, the sequencing of the cucumber genome (Huang et al 2009) has opened the possibility for additional genomic scale studies such as proteomic responses of roots to Fe deficiency (Donnini et al 2010;Li and Schmidt 2010). The rapid growth and relatively large size of cucumber organs offers advantages over Arabidopsis thaliana for certain lines of inquiry.…”
Section: Introductionmentioning
confidence: 99%